Design and Build The Dokestrans Application For Document Management of The Perum Damri Safety Management System - Moh. Adam Asshofi; Joko Siswanto; Nurul Fitriani (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2024)
The Safety Management System (SMK) documents at the Public Transportation Company (PAU) Perum Damri are currently stored using Google Drive, leading to inefficiencies such as document loss, difficulty in locating specific files, and disorganized storage. These challenges hinder the effective compilation and management of SMK PAU documents, potentially impacting safety and compliance standards. To address these issues, the